A Prime-Representing Constant. Issue 1 (2nd January 2019) - Fridman, Dylan; Garbulsky, Juli; Glecer, Bruno; Grime, James; Florentin, Massi Tron
Abstract: We present a constant and a recursive relation to define a sequence fn such that the floor of fn is the n th prime. Therefore, this constant generates the complete sequence of primes. We also show this constant is irrational and consider other sequences that can be generated using the same method.